2016
DOI: 10.3109/21691401.2016.1160406
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and investigation of a novel levobupivacaine in situ implant gel for prolonged local anesthetics

Abstract: In this study, levobupivacaine (LBP) was successfully incorporated into implant application based on the concept of in situ gel (PECE). The physicochemical characterization (preparation, phase transition temperature, in vitro release) were investigated. The results of viscosity measurement showed that the preparations behaved like a fluid but formed a rigid gel when exposed to increasing temperature (37 °C). In vitro release, LBP was graduated released from the gels as time lapsed, suggesting that LBP was well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Even though the injection of local anesthetic agents able to cause reversible nerve blockage is routinely used to reduce postsurgical pain and other pain‐intensive conditions, they become ineffective after a few short hours. In many instances, this limitation is simply, but also inadequately dealt with, by increasing the anesthetics dose . Recently, environmentally responsive polymers, especially reverse thermo‐responsive gels were used as injectable drug delivery systems .…”
Section: Physical Phenomenamentioning
confidence: 99%
“…Even though the injection of local anesthetic agents able to cause reversible nerve blockage is routinely used to reduce postsurgical pain and other pain‐intensive conditions, they become ineffective after a few short hours. In many instances, this limitation is simply, but also inadequately dealt with, by increasing the anesthetics dose . Recently, environmentally responsive polymers, especially reverse thermo‐responsive gels were used as injectable drug delivery systems .…”
Section: Physical Phenomenamentioning
confidence: 99%
“…Organogels are formed by structurants of low molecular weight and some organic solvents that are supported, through a three-dimensional network, forming the gel. Since organogels are biodegradable, they can be used in drugs as protein carriers and vaccines for example [33][34][35].…”
Section: Definitions and Mechanismsmentioning
confidence: 99%
“…In recent years, efforts to develop a novel long-acting local anesthetic included research on new drug molecules (Padera et al, 2006; Lim et al, 2007; Ries et al, 2009; Rodriguez-Navarro et al, 2011; Banerjee et al, 2015; Zhang et al, 2017b), adjuvant drugs (Kito et al, 1998; Sakamoto et al, 2016; Zhang et al, 2018), and sustained-release formulations (Ohri et al, 2013; Ramos Campos et al, 2013; Burbridge and Jaffe, 2015; Zhao et al, 2017b). In previous studies, we showed that QX-OH (Invention Patent, China, ZL201410688865.1), a quaternary lidocaine derivative, maintained the local anesthetic effect over a long period in rats (Zhang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%